1983
DOI: 10.1016/s0022-5347(17)51768-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of Erection in the Monkey

Abstract: Being able to induce controlled erection in dogs and monkeys, we investigated the hemodynamics and mechanism of penile erection. 'Chronic' monkey models, having had electrodes implanted around the cavernous nerves for electroerection, were studied to evaluate the details of the hemodynamic changes. The studies included: 1) arterial blood flow, 2) corporeal pressure, 3) blood gases, 4) venous flow and 5) radiography. Tumescence of the corpora cavernosa was found to be a result of: 1) active relaxation of the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
21

Year Published

1985
1985
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(123 citation statements)
references
References 5 publications
6
96
0
21
Order By: Relevance
“…7,8 Canine models have demonstrated speci®c anatomical changes during penile erection. 9 Arteriolar constriction and sinusoidal contraction occur with¯accidity.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Canine models have demonstrated speci®c anatomical changes during penile erection. 9 Arteriolar constriction and sinusoidal contraction occur with¯accidity.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,9,10,11,13 Sattar et al 11 reported that after injection of PGE 1 , the mean cavernous pO 2 in the control group was signi®cantly different from that in the venogenic and the arteriogenic groups. Furthermore, our data reveal that the femoral artery pO 2 results as well as cavernous pO 2 and sO 2 results following intracavernosal papaverine injection were different in patients with organic erectile dysfunction compared to patients with psychogenic erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accord with investigators who hold the view that electrostimulation of the cavernous nerve, which is autonomic, induces changes in blood¯ow, culminating in full erection with an intracorporeal pressure below the systolic blood pressure. 33 Stimulation of the pudendal nerve, which is somatic, causes contraction of the ischiocavernosus muscle which raises the intracorporeal pressure to above the systolic blood pressure. 33 The question may arise of why did the patients respond with full erections to CN stimulation, but not to intracavernous pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%